Value Management: A Strategic Approach for Reducing Faulty Design and Maintainability Issue in IBS Building - Mohd Nawi, Mohd Nasrun; Radzuan, Kamaruddin; Salleh, Nurul Azita; S.H, Ibrahim (AENSI, 2014)
Maintenance is a combination of all technical and administrative actions including supervision actions, intended to retain an item in or restore it to a state in which it can perform a required function. Value management is a proactive, creative, problemsolving service, using a multi-disciplinary team-oriented approach to make explicit the client?s value system using function analysis to expose the relationship between time, cost and quality with the aim of maximizing the overall performance of an organization. While prevention maintenance means steps taken perhaps in the design of building to make sure it require less maintenance. Meeting the high demand of building in a short time, it is expected that many errors and defects have occurred during the design and construction stages which will result later in high maintenance costs. In order to overcome that issue, this paper will proposed an alternative solution method which more focuses on the building planning design stage. The concept of prevention maintenance will be discuss effectively during the job plan stage of the value management workshop which involve particular parties to reduce unnecessary maintenance costs and faulty design while improving building performance. Suggestions on how value management approach through it systematic workshop in order to minimise the design and maintainability issue will be concluded